Reducing the vulnerability of the Former Yugoslav Republic of Macedonia's agricultural systems to climate change : impact assessment and adaptation options - Sutton, William R., 1967- (World Bank studies., 2013)
Agriculture is one of the most climate-sensitive of all economic sectors. In many countries, such as in FYR Macedonia, the risks of climate change are an immediate and fundamental problem because the majority of the rural population depends either directly or indirectly on agriculture for their livelihoods. The risks of climate change to agriculture in FYR Macedonia cannot be effectively dealt with-and the opportunities cannot be effectively exploited-without a clear plan for aligning agricultural policies with climate change, developing the capabilities of key agricultural institutions, and making needed investments in infrastructure, support services and on-farm improvements.